Relationship between Gerotranscendence and Quality of Life in the Elderly with Cancer - Razie Sadat Hosseiny; Ameneh Mollaei; Masoumeh Alijanpour Aghamaleki (مجله دانشگاه علوم پزشکی گرگان, 2023)
Razie Sadat Hosseiny , Ameneh Mollaei * , Masoumeh Alijanpour Aghamaleki